The Effect of CPEC Energy Projects on Pakistan’s Economic Development - Akash Khan, (Journal of Peace, Development and Communication, 2022)
The China-Pakistan Economic Corridor (CPEC) project is one of the key Belt and Road Initiative (BRI) projects, which is also known as One Belt, One Road (OBOR), and is anticipated to significantly alter the regional economy. The main goal of the current study is to determine how the CPEC energy projects would affect Pakistan's socioeconomic growth. Also included in this study piece are the dangers and difficulties that Pakistan's economy may face as a result of CPEC. The urgent requirement of the hour is to draw attention to the CPEC's key problems. A variety of publications, including newspapers, magazines, journals, research articles, reports, and seminars, have been used to collect data. Pakistan has been experiencing an energy problem for the past 20 years, and the CPEC has made a significant $35 billion investment in the energy industry. Industrial parks, employment opportunities, regional integration, infrastructure development, transportation, FDI, cross-cultural interaction, tourism, etc. are just a few of the areas where CPEC is having a significant impact. Even with all of these benefits, there are still some problems, like security, political agreement, terrorism, fair funding distribution, stabilising local businesses, etc.